Optical Properties and Electronic Band Structures of Perovskite-Type Ferroelectric and Conductive Metallic Oxide Films - Hu, Zhigao; Li, Yawei; Li, Wenwu; Zhu, Jiajun; Zhu, Min; Zhu, Ziqiang; Chu, Junhao (IntechOpen, 2010)
None